Pengaruh Debt To Equity Ratio (DER), Total Asset Turnover (TATO) Dan Net Profit Margin (NPM), Terhadap Return On Equity (ROE) Pada Sub Sektor Transportasi & Logistik Yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2024 - Asep Saepuloh; Alfiana (Indo Publishing, 2026)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Total Asset Turnover (TATO), and Net Profit Margin (NPM) on Return On Equity (ROE) in transportation and logistics sub-sector companies listed on the Indonesia Stock Exchange for the 2021–2024 period. Using the panel data regression method with a sample of 13 companies and a total of 52 observations, this study determined the Common Effect Model (CEM) as the best model based on a series of model selection tests. The research data met the requirements of classical assumption tests, being free from multicollinerity and heteroscedasticity issues. Partial test results (t-test) indicate that the DER variable has a positive and significant effect on ROE. Meanwhile, the TATO variable does not have a significant effect on ROE , and the NPM variable shows a significant effect but with a negative coefficient direction toward ROE in this sub-sector. Simultaneously (F-test), the variables DER, TATO, and NPM collectively affect ROE. The coefficient of determination (Adjusted R Square) of 0.5305 indicates that the independent variables in this study can explain the ROE variable by 53.05%, while the remainder is explained by other factors outside the model.